2016
DOI: 10.1590/1983-084x/15_098
|View full text |Cite
|
Sign up to set email alerts
|

Induction and growth pattern of callus from Piper permucronatum leaves

Abstract: ABSTRACT:Piper permucronatum is a perennial shrub, a medicinal plant native to the Amazon Rainforest. Traditionally, the tea of its leaves is used to combat menstrual and intestinal cramps, stomach pain, digestive problems, diarrhea, hemorrhage, and nausea. Its leaf's essential oil is effective against Aedes aegypti larvae; its flavones and flavanones have a fungicidal effect against Clamidosporium cladosporioides and C. sphaerospermum; its hexanic extract is effective against Leishmania amazonensis. The objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
3
0
2
Order By: Relevance
“…Concentrations below and above 2.0 mg/l 2,4-D reduced callus formation. Various reports have shown that MS medium containing 2,4-D is most effective for induction of callus and development, such as Subasinghe et al (2004) and Hussain et al (2011) in the case of P. nigrum; Delgado-Paredes et al (2013) in the case of P. cernuum and P. aduncum; Santos et al (2015) in the case of P. permucronatum. However, in this study, during the direct shoot induction experiment, it was found that gelled MS medium conjugated with 1.0 mg/l BAP and 1.0 mg/l NAA induced some calli from the nodal segments (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Concentrations below and above 2.0 mg/l 2,4-D reduced callus formation. Various reports have shown that MS medium containing 2,4-D is most effective for induction of callus and development, such as Subasinghe et al (2004) and Hussain et al (2011) in the case of P. nigrum; Delgado-Paredes et al (2013) in the case of P. cernuum and P. aduncum; Santos et al (2015) in the case of P. permucronatum. However, in this study, during the direct shoot induction experiment, it was found that gelled MS medium conjugated with 1.0 mg/l BAP and 1.0 mg/l NAA induced some calli from the nodal segments (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Neste intervalo verificou-se leve aumento na taxa de crescimento quando comparado à fase anterior. O início desta fase é marcado pelo aumento das divisões celulares, comportamento que, diferentemente da Cenostigma pyramidale, em explantes foliares de Piper permucronatum, expressou-se do 21º ao 49º dia de cultivo (SANTOS et al, 2016). Entretanto, em calos de aroeira-do-sertão, partindo de explantes foliares e considerando a sua característica lenhosa, a fase exponencial ocorreu exatamente do 7º ao 28º período de cultivo, comportamento similar ao da espécie em estudo (SILVA et al, 2020).…”
Section: Resultsunclassified
“…A interpretação da curva de crescimento dos calos de catingueira revelou que do 56º ao 63º dia de cultivo iniciou-se a fase de desaceleração (Figura 2) com taxa de crescimento que chegou a 5,57%, período extremamente relevante ao estudo, que se caracteriza pela redução das divisões celulares, maior produção de metabólitos secundários e, principalmente, marca o momento que deve ser iniciado o processo de repicagem dos calos (PAN et al, 2020). O início do processo de repicagem deve ocorrer na fase de desaceleração devido à redução de nutrientes, produção de compostos tóxicos, secagem do ágar e redução do oxigênio no interior das células (SANTOS et al, 2016).…”
Section: Resultsunclassified
“…The results of the cell suspension culture of Piper permucronatum and Piper solanum showed an increase in secondary metabolites, also in the callus of other plants (Santos et al, 2016); (Balbuena et al, 2009); (Jamil et al, 2018); (Khanpour-Ardestani et al, 2015). Callus extracts from cell suspension cultures of Nigella sativa L. were reported to have optimum antimicrobial and antioxidant activity (Chaudhry et al, 2015).…”
Section: Introductionmentioning
confidence: 96%
“…Piper plant consists of more than 1000 species scattered in various tropical regions, several species of this genus are used as food, medicine, stimulant, analgesic, anti-inflammatory, antiseptic, antidepressant, and antioxidant (Meena et al, 2010); (Santos et al, 2016). Various extracts of Piper have high antioxidant activity (Barua et al, 2014); (Akbar et al, 2014); (Hafizah et al, 2010); (Anggreni et al, 2019); (Dasgupta & De, 2004).…”
Section: Introductionmentioning
confidence: 99%